(untitled) (Technological Innovations Journal, 2023)
The issue of carrying bladed weapons in the locality of Kennedy impacts coexistence and public safety, accounting for 77% of thefts and 40% of homicides. This phenomenon is primarily due to the ease of concealing these weapons. Thus, the question arises: How could a more effective registration, utilizing an electronic device, reduce the carrying of bladed weapons? In this context, the general objective proposed is the implementation of a metal detector to prevent crimes involving bladed weapons. The study design is exploratory, based on the Design Thinking methodology, encompassing stages of empathy, definition, ideation, prototyping, and testing. The results indicate that the implementation of a modified flashlight with a metal detector has proven effective in preventing crime in the locality of Kennedy, Colombia, which has experienced exponential growth due to the increasing demand for bladed weapons, their illegal carrying, and the emergence of disruptive behaviors in coexistence. This device has proven effective in detecting bladed weapons thanks to the characteristics of its flashlight format. It utilizes brightness to identify objects, complemented by an audible and vibrational alarm system that caters to the needs of the police service.